Business Architecture TOGAF ADM Case Study: Desa Bungin Office - Sister, Maya Gian; Hikmah , Maulida; Imelda (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
Desa Bungin, located in the Paringin Selatan District of Balangan Regency, has begun adopting information technology to enhance administrative activities. However, administrative management at the Desa Bungin Office still faces several challenges, including manual record-keeping, reliance on hard-copy archives, and dependence on a centralized system without an integrated information system. These limitations result in inefficiencies in time management, an increased risk of errors, and obstacles to providing optimal administrative services to the community. To address these issues, this study proposes an enterprise architecture framework to align business functions with information technology needs. The TOGAF ADM approach is employed as a structured methodology for developing an integrated architectural blueprint. This study focuses on three key phases of TOGAF ADM: the Preliminary Phase, Architecture Vision, and Business Architecture, with a strong emphasis on Business Architecture design. Business Architecture plays a crucial role in structuring and analyzing business processes, identifying key actors, and understanding interactions within the organization. This research examines essential elements such as workflows, resources, and inter-process relationships. The findings present a well-structured Business Architecture model that serves as the foundation for developing a comprehensive Enterprise Architecture. This framework is expected to enhance efficiency, streamline administrative processes, and support the digital transformation of Desa Bungin’s governance.